The complex nature of heterogeneity and its roles in breast cancer biology and therapeutic responsiveness - Andrade de Oliveira, Karla; Sengupta, Surojeet; Yadav, Anil Kumar; Clarke, Robert (Frontiers in Endocrinology, 2023)
Heterogeneity is a complex feature of cells and tissues with many interacting components. Depending on the nature of the research context, interacting features of cellular, drug response, genetic, molecular, spatial, temporal, and vascular heterogeneity may be present. We describe the various forms of heterogeneity with examples of their interactions and how they play a role in affecting cellular phenotype and drug responses in breast cancer. While cellular heterogeneity may be the most widely described and invoked, many forms of heterogeneity are evident within the tumor microenvironment and affect responses to the endocrine and cytotoxic drugs widely used in standard clinical care. Drug response heterogeneity is a critical determinant of clinical response and curative potential and also is multifaceted when encountered. The interactive nature of some forms of heterogeneity is readily apparent. For example, the process of metastasis has the properties of both temporal and spatial heterogeneity within the host, whereas each individual metastatic deposit may exhibit cellular, genetic, molecular, and vascular heterogeneity. This review provides insight into the many forms of heterogeneity, their integrated activities, and offers some insights into how heterogeneity may be understood and studied in the future.